2003
DOI: 10.1046/j.1365-2842.2003.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

The condylar asymmetry measurements in different skeletal patterns

Abstract: In the present study, condylar asymmetry measurements were investigated on the lateral cephalometric head radiographs and the panoramic radiographs of 72 subjects (36 males and 36 females), aged 12-16-years and having different skeletal patterns. The lateral cephalometric head radiographs were divided into three groups according to the ANB angle: ANB angles smaller than 1 degrees, between 1 degrees and 5 degrees, and larger than 5 degrees. In addition, each group was also divided into two subgroups according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
4
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 21 publications
4
36
4
4
Order By: Relevance
“…9,15 In this study, no gender related statistically significant differences were found between compared sides and investigated groups. These findings support the studies of Habets et al, 9 Kiki et al 17 and Sezgin et al 18 that used the same method described in the present study.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…9,15 In this study, no gender related statistically significant differences were found between compared sides and investigated groups. These findings support the studies of Habets et al, 9 Kiki et al 17 and Sezgin et al 18 that used the same method described in the present study.…”
Section: Discussionmentioning
confidence: 51%
“…[9][10][11][12][13][14][15][16][17][18] Bilateral views of the mandible can be obtained with OPG, and vertical measurements can be achieved. 20 The use of panoramic radiographs to evaluate side-to-side differences is questionable, but a number of studies have been made that supported the use of the panoramic technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability of this formula has been shown in many studies (Habets et al 1988, Saglam 2003, Kiki et al 2007, Kilic et al 2008. The formula and method to assess the condylar and ramal asymmetry described by Habets et al (1988) has also been used in many studies.…”
Section: Discussionmentioning
confidence: 86%
“…It has also been used for the assessment of side-to-side dimensional differences and to define the asymmetries (Habets et al 1987, Miller et al 1996, Miller et al 1997, Saglam 2003, Kiki et al 2007, Sezgin et al 2007, Kurt et al 2008. The use of OPG for specific measurements and the determination of differences is controversial owing to considerations relating to magnification and distortion.…”
Section: Discussionmentioning
confidence: 99%